USAGE OF UZBEK APPLIED ARTS IN MODERN HOTELS (Conference Zone, 2022)
This article provides general information and addresses questions about the revival of the traditions of handicraft production, the desire for preservation of the national culture of the Region. It also highlights the main types and originality of applied art of Uzbekistan. The authors give new information about local craftsmen, each with different styles ornamental and color solutions